2018
DOI: 10.1039/c8ra02062k
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in physical properties of single-layer gas diffusion layers using graphene for proton exchange membrane fuel cells

Abstract: Gas diffusion layer (GDL) is an important component related to the efficiency of proton exchange membrane fuel cells (PEMFCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The improvements in the physical properties have shown a significant increase in the cell power densities and improved performance. 33 In 2018, Ozden et al, 34 used graphene in the MPL layer composition to improve GDL properties. The MPL was made by spray deposition of graphene (G-MPL) and morphological, microstructural, physical, electrochemical properties, and the PEMFC performance were investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvements in the physical properties have shown a significant increase in the cell power densities and improved performance. 33 In 2018, Ozden et al, 34 used graphene in the MPL layer composition to improve GDL properties. The MPL was made by spray deposition of graphene (G-MPL) and morphological, microstructural, physical, electrochemical properties, and the PEMFC performance were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 32 coated graphene on nickel foam through chemical vapor deposition and showed that the corrosion problem reduced by ninefold, and the contact angle increased by 35% compared with the uncoated foams. By adding carbon nanofibers and graphene to a carbon black‐PTFE composite in a relatively simple and inexpensive process, a series of highly efficient monolayer graphene‐containing, single‐layer GDLs (SL‐GDLs) were successfully prepared by Lee et al 33 The fabricated GDLs showed improved properties such as low electrical resistivity, large average pore sizes, rough surface, and excellent mechanical properties. The improvements in the physical properties have shown a significant increase in the cell power densities and improved performance 33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] The GDL is a key component of water and gas management in PEMFC, and has been extensively studied and explored. 11,12 In the current process of GDL research, the thickness, pore size, porosity, and hydrophobicity of GDL are mainly involved.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 19 studied the use of graphene oxide reinforced ultra thin carbon paper for fabricating gas diffusion layers. Lee et al 20 proposed the employ of an improved single layer as gas diffusion layer in a fuel cell after graphene incorporation to its composition. Tabe et al 21 studied the impact of the micro porous layer morphology and on the liquid water distribution at the catalyst interface and how this affect to the fuel cell performance.…”
Section: Introductionmentioning
confidence: 99%